Strain measurements and fracture resistance of endodontically treated premolars restored with all-ceramic restorations. Issue 1 (January 2015) - Seow, Liang Lin; Toh, Chooi Gait; Wilson, Nairn H.F.
Abstract Objectives The aim of this study was to investigate the recovery of cuspal stiffness and fracture resistance in endodontically treated maxillary premolars restored with bonded ceramic inlays and onlays of various designs. Methods Seventy intact premolars were selected for this study; six cavity designs were investigated: (i) mesio-occlusal-distal (MOD) inlay (I), (ii) MOD inlay with palatal cusp coverage (IPC), (iii) MOD onlay (O), (iv) MOD inlay with pulp chamber extension (IPE), (v) MOD inlay with palatal cusp coverage and pulp chamber extension (IPCPE), and (vi) MOD onlay with pulp chamber extension (OPE). Intact teeth acted as control. Strain gauges were attached to the buccal and palatal surfaces of the teeth to measure cuspal stiffness under static loading. All specimens were eventually subjected to compressive load to failure. Cuspal stiffness and fracture resistance data were analyzed using ANOVA and Tukey test. Results The I and IPE restorations restored cuspal stiffness to 75% of the sound tooth value. The O and OPE restored teeth had stiffness values greater than that of a sound tooth. The I, IPC, O, IPE, IPCPE and OPE restored teeth demonstrated fracture strength values of 938 N ± 113 N (s.d.), 1073 N ± 176 N and 1317 N ± 219 N, 893 N ± 129 N, 1062 N ± 153 N and 1347 N ± 191 N respectively. Conclusions Within the limitations of this study, it was concluded that the all-ceramic onlay or inlay with palatal cusp coverage provided best biomechanical advantage in restoring an endodontically treated maxillary premolar tooth. Clinical significance The onlay approach which is more conservative compared to full coverage restoration is considered an appropriate approach to the restoration of endodontically treated maxillary premolars. The addition of a pulpal extension to the all-ceramic restorations, apart from being technically challenging, was not found to offer any biomechanical advantage to the restored teeth.